Pemodelan Dan Simulasi Dinamika Kendaraan Roda 4 Dengan Metode Bondgraph Untuk Pengembangan Simulator Dinamik - Felix Renaldi (Jurusan Teknik Industri, Fakultas Teknologi Indusri Universitas Trisakti, 2011)
This paper discussed the dynamics and modeling of the wheel 4 vehicle using bondgraph method. Bondgraph method is a method of modeling dynamic system using a united approach. With this method, the model of a dynamic system formed by observing the flow of energy exchange that occurs in advance of system components. United approach used in this method allows the system to different domains can be modeled in an integrated way. On the development of dynamic models of four-wheel vehicles, the dynamics equations in two areas, namely the lateral and longitudinal, are modeled with bondgraph components, and is equipped with a kinematic equation to the directional field. Bondgraph model can then be simulated using the software SIMULINK. For the purposes of developing a four-wheeled vehicle simulator, a four-wheeled vehicle types modeled and simulated using this approach. The results obtained show equivalence with the expected physical phenomena. In a further step, an initial configuration of the simulator platform is designed with attention to major degrees of freedom dynamical system modeled by equations. Mechanical platform is then modeled with the software SIMMECHANICS to evaluate its ability to reconstruct the main motion of four-wheeled vehicles that were examined. With these simulations, the capabilities and limitations of the platform configuration can be analyzed.